Association of affective disorders and MTHFR, MTR, and MTRR gene polymorphisms: preliminary results of a family study - E. D. Kasyanov; T. V. Zhilyaeva; G. E. Maso (Неврология, нейропсихиатрия, психосоматика, 2022)
Genetic polymorphisms associated with impaired one-carbon metabolism (1-CM) can be a risk factor not only for somatic and neurological diseases, but also for affective disorders (AD).Objective: to compare the frequency of genetic polymorphisms MTHFR, MTR, MTRR associated with 1-CM disorders among patients with AD, their blood relatives and healthy individuals.Patients and methods. This cross-sectional study of the frequency of genetic polymorphisms (MTHFR, MTR, MTRR) associated with 1-CM included patients with AD (n=24), their blood relatives (n=40), as well as a group of healthy individuals (n=35). All study participants underwent a structured diagnostic interview, as well as genetic analysis using real-time polymerase chain reaction.Results and discussion. Patients with AD were statistically more likely to carry the minor allele C of the 1298A>C polymorphism of the MTHFR gene and the minor allele G of the 2756A>G polymorphism of the MTR gene compared to the group of healthy individuals. The minor allele T of the 677C>T polymorphism of the MTHFR gene was associated with longer depressive episodes, as well as with the presence of concomitant cardiovascular diseases in blood relatives of patients with AD.Conclusion. Genetic polymorphisms associated with 1-CM may contribute to familial aggregation of AD and somatic diseases. Further highquality family studies using molecular genetic methods are needed.